PEMBUATAN KRIM DENGAN BAHAN TAMBAHAN VIRGIN COCONUT OIL DAN ENFLEURAT RAMBUT JAGUNG (ZEA MAYS L.) UNTUK PENGETAHUAN DINI DI MASYARAKAT - Suaniti, N.M.; Riasa, I.N.P.; Adnyana, I.W.B.; Bogoriani, N.W.; Suarda, I.M.; Wijana, A.J.Y.A.; Lestari, N.M.W.M.; Suadnyana, I.P.R.; Maharani, N.M.S.; Sari, N.K.I.C.P. (Buletin Udayana Mengabdi, 2024)
Cream as a cosmetic product can be made with the addition of virgin coconut oil (VCO) and corn hair, as part of the natural ingredients available in Mambang Village, East Selemadeg Tabanan Bali.  The purpose of this service is to make cream with VCO additives and corn hair enfleurat as well as socialize the results of VCO and cream research as one of the environmentally friendly products and early knowledge in the community. This Udayana Mengabdi (PUM) service activity was carried out with students from various study programs at Udayana University and the community (PKK mothers) in Banjar Pulu Tengah, Mambang village on the XXVII Community Empowerment Learning Real Work Lecture (KKN-PPM). The cream obtained a good color and preferred texture both directly and through questionnaire results. The community response is good and enthusiastic about this service activity, organoleptically such as color, aroma and texture of the cream is preferred, pungent, and easy to absorb. Keywords: community, corn hair, cream, enfleurat, Virgin coconut oil.